1956
DOI: 10.1063/1.1742460
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Spectra of Some Mixed Halides of Boron

Abstract: Mixed halides of boron have been shown to exist in binary mixtures of the trihalides. Most of the fundamental frequencies of BF2CI, BFCb, BF.Br, BFBr2, BCbBr, and BCIBrz for molecules containing boron-lO and boron-ll have been observed and assigned to the proper modes of vibration. With the aid of the trihalide frequencies a normal coordinate treatment has been made for the mixed halides. Some discussion of the validity of transferring force constants in this system has been given.* Dr. Felix Smith has kindly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1959
1959
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“….478 (9) .454( 10) .365 ( 11) 119.3 (7) 148.0( 7) 1 13.8(3) 1 I2.7(3) 7 1.1(8) 106. 4( 3) less reactive than the sterically hindered arylboronic acids B(C,HzR,-2,4.6)(OH), (R = Me" or Butl8) both of which can be dehydrated, though with difficulty, on heating.…”
Section: Resultsmentioning
confidence: 99%
“….478 (9) .454( 10) .365 ( 11) 119.3 (7) 148.0( 7) 1 13.8(3) 1 I2.7(3) 7 1.1(8) 106. 4( 3) less reactive than the sterically hindered arylboronic acids B(C,HzR,-2,4.6)(OH), (R = Me" or Butl8) both of which can be dehydrated, though with difficulty, on heating.…”
Section: Resultsmentioning
confidence: 99%
“…When argon- matrix samples with prominent negative ion and 1037cm-I absorptions are subjected to a brief period of mercury-arc irradiation, these absorptions are greatly diminished in intensity. The appearance of these absorptions under similar conditions is consistent with the hypothesis that the 1037-cm-1 absorption is contributed by a positively charged species which is responsible for maintaining over-all charge neutrality of the sample, The disappearance not only of the negatively charged species but also of the species which contributes the 1037-cm-1 absorption when the sample is subjected to mercury-arc irradiation could be understood by postulating photodetachment of the electron from the negatively charged species and electron capture by the positively charged species, As has already been noted, an appreciable concentration of CCIa is produced on 1216-A photolysis of chloroform in an inert, rigid matrix, and the energy available from the photolysis lamp is considerably in excess of the ionization potential of CCla, Thus, one might expect secondary photoproctisses to lead to the production of CCla+ in such experiments, The behavior of the 1037cm-I absorption in the isotopic substitution experiments is entirely consistent with the assignment of this absorption to CC/a+, The experiments on carbon-13 enriched samples have demonstrated that only a single carbon atom participates in the vibration of interest, and the absorption is completely insensitive to the substitution of deuterium in the chloroform molecule, suggesting that the product species may possess no hydrogen atoms, Furthermore, the two major peaks are in the 3: 1 relative intensity ratio expected either for the chlorine-isotopic contributions to the C-Cl stretching absorption of a molecule possessing a single chlorine atom or for the doubly degenerate C-Cl stretching fundamental of a molecule which possesses three symmetrically equivalent chlorine atoms, 19,20 The semieQlpirical molecular orbital treatment of Walsh 21 for ABa species possessing a threefold axis of symmetry predicts that CCla+, with 24 valence electrons, should be planar in its ground state. This prediction has been found to be consistent with the planar structure observed for a number of other 24-valenceelectron species, including BFa and BCla, Planarity of the molecule would also be consistent with the failure to observe any absorption attributable to the nondegenerate C-Cl stretching fundamental, VI, despite the considerable intensity of the degenerate C-Cl stretching fundamental, Va.…”
Section: Spectrum Of Cc1a+mentioning
confidence: 97%
“…The observed force-constant K,, was broken down into contributions from the individual peripheral atoms,* i.e., K,,(COXY) = K, + Ky + KO. (1) * This approach is not without precedent ; Lindemann and Wilson 21 …”
Section: Ch3chomentioning
confidence: 99%